Fostering Community Wellness Through Nutrition and Physical Activity at K-State Research and Extension - Weinrich, Shely (My University, 2011)
Amongst adults and children, obesity has been on the rise in multiple countries, bringing obesity to the forefront of public health. Obesity has been shown to be correlated with multiple chronic conditions such as diabetes, cardiovascular disease, and metabolic disorders. Furthermore, those who are lower socioeconomic status (SES) and from a minority background are significantly more likely to have multiple health conditions than their higher SES and white counterparts (Tucker-Seeley, Li, Sorensen, & Sabramanian, 2011). Additionally, children and adults of low SES are more likely to be less physically active and have higher rates of obesity (Burgi, et al., 2010; Dubois & Girard, 2006; Semmler, Ascroft, van Jarrsveld, Carnell, & Wardle, 2008). Of the numerous risk factors for multiple chronic conditions, nutrition and physical activity have been shown to reduce the effects of obesity and its related co-morbidities (e.g., diabetes). One way to curb obesity and its related co-morbidities is by providing education and skill training on proper eating and how to engage in more physical activity. Consequently, this paper will focus primarily on the Expanded Food and Nutrition Education Program implemented during my internship with K-State Research and Extension (KSRE). Additionally, my other activities completed during my internship will be discussed, including worksite wellness and community programs.
Keywords: Obesity; Extension; Food and Nutrition; Assistance Programs; Wellness; Public Health (0573)